Focal Urethral Stricturing Following Intraurethral Mitomycin-C Gel and the Use of a Penile Clamp - Richard F. J. Stanford; Stephen A. Thomas (Case Reports in Urology)
We present a case of a 51-year-old gentleman, previously diagnosed with high-grade superficial transitional cell carcinoma of the bladder and treated with intravesical mitomycin C and BCG, who developed serial recurrences in the prostatic urethra. This was resected and treated further with intraurethral mitomycin-C gel. He subsequently developed an almost impassable distal penile urethral stricture, corresponding to the site of penile clamp application which we hypothesise is secondary to a combination of the mitomycin-C gel and penile clamp pressure.